Urethral Erosion and Perineal Cellulitis after Midurethral Sling Procedure - Kim, Jong Min; Bae, Jang Ho; Song, Phil Hyun; Shin, Esther; Jung, Hee Chang (International neurourology journal, 2011)
Midurethral tension-free sling procedure has become one of the most popular techniques for the treatment of stress urinary incontinence. As the time elapsed, however, complications associated with a synthetic tape have been reported to occur. Recently, we experienced a rare case of urethral erosion with perineal cellulitis at anterior wall of vagina after midurethral sling procedure. So our experience was presented with a review of literature.